2005
DOI: 10.4049/jimmunol.175.7.4754
|View full text |Cite
|
Sign up to set email alerts
|

CD44 and Annexin A2 Mediate the C5a Chemotactic Cofactor Function of the Vitamin D Binding Protein

Abstract: The vitamin D binding protein (DBP) is a plasma protein that significantly enhances the chemotactic activity of C5a and C5adesArg (cochemotactic activity). The objective of this study was to investigate how DBP mediates this process using neutrophils and U937 cells transfected with the C5a receptor (U937-C5aR cells) and comparing chemotaxis to C-activated serum (DBP dependent) vs purified C5a (DBP independent). Binding to the cell surface is essential for this protein to function as a chemotactic cofactor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…Plasma-derived DBP also binds to the surface of many cell types including neutrophils (DiMartino and Kew, 1999;DiMartino et al, 2001;White and Cooke, 2000). DBP appears to bind with low affinity to multiple cell surface ligands such as chondroitin sulfate proteoglycans (DiMartino and Kew, 1999), megalin (Nykjaer et al, 1999;Nykjaer et al, 2001), cubulin (Nykjaer et al, 2001), CD44 and annexin A2 (McVoy and Kew, 2005). Neutrophils transiently generate co-chemotactic activity for C5a on the cell surface within 15-20 min of DBP binding (Kew et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma-derived DBP also binds to the surface of many cell types including neutrophils (DiMartino and Kew, 1999;DiMartino et al, 2001;White and Cooke, 2000). DBP appears to bind with low affinity to multiple cell surface ligands such as chondroitin sulfate proteoglycans (DiMartino and Kew, 1999), megalin (Nykjaer et al, 1999;Nykjaer et al, 2001), cubulin (Nykjaer et al, 2001), CD44 and annexin A2 (McVoy and Kew, 2005). Neutrophils transiently generate co-chemotactic activity for C5a on the cell surface within 15-20 min of DBP binding (Kew et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…AP on the external face of the plasma membrane also has been shown to associate with annexin A2 in lipid rafts (Gillette and Nielsen-Preiss, 2004). Moreover, our lab has recently shown that annexin A2 may serve as part of the DBP cell surface binding site (McVoy and Kew, 2005). These studies have provided the rationale to investigate if there is an association between 1,25(OH) 2 D 3 and AP.…”
Section: Resultsmentioning
confidence: 96%
“…Several studies from our laboratory have demonstrated that the binding of DBP to the neutrophil plasma membrane, and subsequent protease-mediated shedding of the binding site, are essential for the chemotaxis enhancement of C5a (DiMartino and Kew, 1999;DiMartino et al, 2001;Kew et al, 1995a;Kew et al, 1995b) More recently, we have demonstrated that DBP requires platelet-derived thrombospondin-1 for maximal cochemotactic activity (Trujillo and Kew, 2004). In addition, cell surface CD44 and annexin A2 are part of a DBP binding site complex and mediate the C5a chemotactic cofactor function of DBP (McVoy and Kew, 2005). The current study provides evidence that the putative cellular binding site on DBP is not altered by ligation with vitamin D sterols or G-actin.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations